1997
DOI: 10.1016/s0092-8674(00)80241-x
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Silencing in Erythroid Differentiation: hnRNP K and hnRNP E1 Regulate 15-Lipoxygenase Translation from the 3′ End

Abstract: Although LOX mRNA accumulates early during differentiation, a differentiation control element in its 3' untranslated region confers translational silencing until late stage erythropoiesis. We have purified two proteins from rabbit reticulocytes that specifically mediate LOX silencing and identified them as hnRNPs K and E1. Transfection of hnRNP K and hnRNP E1 into HeLa cells specifically silenced the translation of reporter mRNAs bearing a differentiation control element in their 3' untranslated region. Silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
439
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(452 citation statements)
references
References 48 publications
8
439
4
Order By: Relevance
“…These properties suggest that K protein bridges signal transduction pathways to nucleic aciddirected processes. In further support of this model, several studies have shown that K protein can alter rates of transcription (Michelotti et al, 1996) and translation (Ostareck et al, 1997).…”
mentioning
confidence: 75%
“…These properties suggest that K protein bridges signal transduction pathways to nucleic aciddirected processes. In further support of this model, several studies have shown that K protein can alter rates of transcription (Michelotti et al, 1996) and translation (Ostareck et al, 1997).…”
mentioning
confidence: 75%
“…Recent work has revealed an unexpected role of several members of the SR protein family, including ASF/SF2 and SRp20, in translational control (Sanford et al, 2004;Bedard et al, 2007). Among the hnRNP family, hnRNP K and hnRNP E1 silence translation of the 15-lipoxygenase (LOX) mRNA in immature erythroid precursor cells (Ostareck et al, 1997). Several hnRNPs, including A1, C1/C2, E1/E2, I (PTB), and L, are independently involved in the translational control of specific mRNAs containing internal ribosome entry sites (IRESs) through a capindependent mechanism (for review, see Vagner et al, 2001;Bonnal et al, 2003;Komar and Hatzoglou, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is a short, but growing, list of genes containing RNA cis-elements that modulate translation: the transcript for FMR protein (Fragile X mental retardation protein) encodes 5 0 UTR secondary structure, which is sufficiently stable to suppress downstream FMR protein translation (Feng et al, 1995), tissue-specific regulation of fibroblast growth factor 2 translation appears to be dependent on its 5 0 UTR (Creancier et al, 2000), 15-lipoxygenase, fibronectin, lipoprotein lipase, folate receptor-a, interferon-g, transforming growth factor-b1, m-numb and neural nitric-oxide synthase (nNOS), among others (Ostareck et al, 1997;Ranganathan et al, 2000;Galy et al, 2001;Morrisey et al, 2001;Imai et al, 2001;Ben-Asouli et al, 2002). Similarly, vascular endothelial growth factor regulation by hypoxia (Stein et al, 1998) and platelet-derived growth factor 2/c-sis expression that occurs during differentiation (Bernstein et al, 1997) are regulated in this way as well.…”
Section: Discussionmentioning
confidence: 99%